Development of teaching materials for making simple energy-producing devices in renewable energy topic - Ilham Fauzi; Mawardi Mawardi; Okta Suryani (Jurnal Pijar Mipa, 2023)
The change in curriculum to a Merdeka Curriculum causes changes in the learning system in Indonesia because this requires teachers and students to be more innovative and creative. To balance this requires teaching materials that can meet these needs, especially renewable energy materials; this material is new, so there are still few teaching materials available. The available renewable energy teaching materials are not carried out in practicum, so teachers still use references to the previous curriculum teaching materials, which are no longer significant. This type of research is educational development research or Educational Design Research (EDR). The stages of development research consist of 3 main stages: preliminary research, prototyping stage, and assessment phase. The development model used in this research is the Plomp development model developed by Tjreed Plomp. The research instruments used were interview sheets and questionnaires in the form of validity sheets which were analyzed with Aiken's V scale and practicality sheets. The validity test results were obtained by Aiken's V scale of 0.93 with high validity, which means that the developed teaching materials are valid. The practicality test results for the small group were 89% with very high practicality. Based on the teacher response questionnaire with very high practicality and obtained 93% based on the student response questionnaire with very high practicality, the teaching materials developed are practical. Based on the study's results, the teaching materials of the Independent Curriculum on renewable energy Phase E are valid and practical.